Mengajarkan Sikap Anti Korupsi Sejak Dini Melalui Refleksi Keluaran 23:1-13 - Rifai Rifai (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2018)
The injustice act of corruption is an apprehensive thing in the national lifes context of Indonesia. There were some treatments and eradication of corruption act had been taken, especially by government, with established a special commission for eradicating corruption. Another important against corruption act is to do an early precaution by giving Christian education lesson in school. This article aimed to describe the using of biblical text on Exodus 23:1-13 as the lesson matter to the student in order they have behavior of anti-corruption. This article used the methods of describing and text analyzing on Exodus 23:1-13. The conclusion is, that the student had to be affected by the values taught in Exodus 23:1-13, they are: not to witness a false report, obeying the rule or law, do justice, love others, not to oppress, and not to call on other God, in order having a behaviour of anti-corruption.AbstrakTindakan kriminal pidana korupsi merupakan hal yang sangat mengkuatirkan dalam kehidupan bangsa Indonesia. Berbagai cara penanganan dan pemberantasan tindak korupsi dilakukan, terutama oleh pemerintah, yaitu dengan membuat komisi khusus untuk memberantas korupsi. Hal yang tidak kalah penting adalah melakukan tindakan pencegahan dini melalui pelajaran Pendidikan Agama Kristen di sekolah. Artikel ini bertujuan untuk memberikan gambaran penggunaan teks Keluaran 23:1-13 sebagai materi ajar kepada siswa agar memiliki sikap anti korupsi. Metode yang digunakan adalah deskripsi dan analisis teks pada Keluaran 23:1-13. Kesimpulannya, anak didik harus menghayati nilai-nilai yang diajarkan dalam Keluaran 23:1-13, seperti: tidak bersaksi dusta, taat hukum atau aturan, berlaku adil, mengasihi, tidak suka memeras, dan tidak menduakan Tuhan, agar memiliki sikap yang anti terhadap segala bentuk tindakan korupsi.